The effect of perspective-taking on reasoning about strong and weak belief-relevant arguments. (3rd April 2017) - McCrudden, Matthew T.; Barnes, Ashleigh; McTigue, Erin M.; Welch, Casey; MacDonald, Eilidh
ABSTRACT: This study investigated whether perspective-taking reduces belief bias independently of argument strength. Belief bias occurs when individuals evaluate belief-consistent arguments more favourably than belief-inconsistent arguments. Undergraduates ( n = 93) read arguments that varied with respect to belief-consistency (i.e., belief-consistent or belief-inconsistent) and strength (i.e., strong or weak) about the topic of climate change. After participants read each argument, those in the perspective-taking condition rated the argument's strength from a perspective of a climate scientist and then from their own perspectives, whereas those in the no perspective-taking condition only rated the arguments from their own perspectives. Perspective-taking eliminated belief bias for weak arguments, but not for strong arguments. Theoretical and practical implications of the results are discussed, and directions for future research are provided.